\(\cfrac{x+y}{x-y}=\cfrac{a}{b}----(i)\)
বা, \(\cfrac{x+y+x-y}{x+y-x+y}=\cfrac{a+b}{a-b}\)
[যোগভাগ প্রক্রিয়া করে পাই]
বা, \(\cfrac{2x}{2y}=\cfrac{a+b}{a-b}\)
বা, \(\cfrac{x}{y}=\cfrac{a+b}{a-b}\)
\(\therefore \cfrac{y}{x}=\cfrac{a-b}{a+b}----(ii)\)
\(\therefore\) বামপক্ষ \(= \cfrac{y^2+xy}{x^2-xy}\)
\(=\cfrac{y(x+x)}{x(x-y)}\)
\(=\cfrac{y}{x}\times \cfrac{x+y}{x-y}\)
\(=\cfrac{a-b}{a+b}\times \cfrac{a}{b}\)
[\((i)\) ও \((ii)\) নং সমীকরনের মান বসিয়ে]
\(=\cfrac{a^2-ab}{ab+b^2} \)
\(=\cfrac{a^2-ab}{b^2+ab} \)
=ডানপক্ষ (প্রমাণিত)